Comparison of the Cutaneous Wound Healing of Ovariectomized Mouse at 12 Weeks with That of SHAM and Estrogen-Administered Mice. (7th July 2014) - Mukai, Kanae; Miyasaka, Yuriko; Takata, Kana; Urai, Tamae; Nakajima, Yukari; Komatsu, Emi; Sugama, Junko; Nakatani, Toshio
Abstract : The aim of this experiment was to investigate the effect of 17β -estradiol on cutaneous wound healing in 12-week ovariectomized (OVX) female mice. Eight-week-old female mice were divided into three groups: administration of 17β -estradiol after OVX (OVX + 17β -estradiol), OVX, and sham (SHAM). Four weeks after surgery, the mice received two full-thickness cutaneous wounds. 17β -Estradiol at 0.01 g/day was administered on the backs of mice in the OVX + 17β -estradiol group every day. Plasma 17β -estradiol level in the OVX + 17β -estradiol group was thus significantly higher than in the SHAM and OVX groups, but there was no significant difference between SHAM and OVX groups. The ratio of wound area was not significantly different among the three groups. However, the period required to reach a ratio of wound area of 0.15 in the OVX + 17β -estradiol group was significantly shorter than in the SHAM and OVX groups. These results indicate that cutaneous wound healing in young OVX mice was promoted by the administration of 17β -estradiol compared with that in SHAM and OVX mice without such administration, but there was no difference between the latter two groups that did not differ in 17β -estradiol level.